Understanding compulsive buying tendencies among young Australians: the roles of money attitudes and credit card usage - Phau, Ian; Woo, Charise (Emerald Group Publishing Limited, 2008)
To investigate money attitudes and credit card usage between compulsive and non-compulsive buyers of young Australians. It also serves to validate the MAS scale using an Australian sample. Data were collected using a mall intercept method in a major shopping complex in Perth, Western Australia. A self-administered questionnaire was distributed and recorded a response rate of 18%. Compulsive buyers are more likely to perceive money as a source of power and prestige. They are also more frequent users of credit cards and are more likely to bargain hunt. There are no differences between compulsive and non-compulsive buyers for the dimensions of time retention, distrust, and anxiety of the MAS scale. The study has only captured young adult Australians and should not be generalised across other demographics and national consumers. Studies on compulsive behaviour of online shopping and a comparison between fashion and non-fashion related variables could also be explored. Firms should consider using advertising campaigns that portray images of status and prestige in order to appeal to young adults. They could utilize aggressive in-store promotion and selling techniques and highlight the discount or best buy slogans. For the credit card companies and banks, word-of-mouth through family and friends are better promotional tools to attract users. Marketers and policy makers are recommended to incorporate consumer education programs for young adults to build skills to counter financial problems. This is the first Australian study that examined money attitudes, credit card usage and compulsive behaviour. Further the MAS scale is validated with the addition of the 'bargain hunting' variable.